Using genomics to trace genealogy in the early stages of forest tree domestication - Jaroslav Klápště; Natalie J. Graham; Heidi S. Dungey; Mari Suontama; Glenn T. Howe (Genetic Resources and Crop Evolution, 2025)
Because climate change is pressuring every terrestrial ecosystem including forests, efficient methods for managing forest genetic resources are needed. One approach is to use molecular genetic markers in tree breeding programmes. Current genotyping tools can be used to improve the selection of genetically superior trees via genomic prediction. However, population structure may affect the prediction of breeding values, particularly in the early stages of tree domestication. We examined how models of population structure affected breeding values using a single-step genomic prediction framework (ssBLUP) in Douglas-fir ( Pseudotsuga menziesii (Mirbel) Franco) in New Zealand. In particular, we tested three metafounder scenarios. The ssBLUP1 scenario assumed there was a single metapopulation. The other scenarios assumed there were multiple metapopulations with either no gene flow (ssBLUP2) or gene flow among populations (ssBLUP3). All three metafounder scenarios performed better than the pedigree-based (ABLUP) and benchmark (ssBLUP) scenarios. The multiple metapopulation scenarios (ssBLUP2 and ssBLUP3) had slightly greater heritabilities than did the ABLUP and ssBLUP approaches, but heritabilities doubled for the single metapopulation scenario (ssBLUP1). The ssBLUP1 scenario also had the largest accuracy of genomic estimated breeding values (GEBV) but also the largest GEBV bias. In contrast, ssBLUP3 had the lowest GEBV accuracy and bias. Results for the ssBLUP2 scenario demonstrated the value of accounting for genetic variation among metafounders. Compared to the single metapopulation scenario (ssBLUP1), ssBLUP2 had lower GEBV bias and smaller underdispersion of GEBV. Finally, our study demonstrated the benefits of selecting ancestry-informative markers (AIM) for use in the ssBLUP model with metafounders. Compared to all markers, the AIM markers were better able to distinguish populations used in the ssBLUP models.

Extreme Heatwave Causes Immediate, Widespread Mortality of Forest Canopy Foliage, Highlighting Modes of Forest Sensitivity to Extreme Heat - Adam Sibley; Christopher Still; Matthew Gregory; Constance Harrington; David Shaw; Nina Ferrari; Alex Dye; Mark Schulze; Glenn Howe; David E. Rupp; Christopher Daly; Daniel DePinte; et al. (Global Change Biology, 2025)
In late June 2021, multiple days of record‐breaking heat caused an unprecedented amount of foliage death in the forests of the Pacific Northwest, USA. Portions of tree canopies with healthy green foliage prior to the heat changed to red or orange shortly after the event. The change in foliage color could be readily seen in satellite imagery and was corroborated as foliar death (heat scorch) by aerial surveys and extensive observations on the ground. To better understand the patterns and processes driving foliar death, we used satellite imagery to identify 293,546 ha of forest, or ~4.7% of forest area, that were damaged in western Oregon and Washington by this extreme heat event. Analysis of underlying drivers of the observed heat damage indicated greater sensitivity was related to abiotic factors such as sun exposure, aspect, and microclimate, as well as biotic factors like tree species and stand age, budburst phenology, and foliar pathogens impacting tree health. Iconic, culturally and economically significant species like western redcedar, western hemlock, and Sitka spruce were disproportionately sensitive to heat damage, including in old‐growth stands where they are canopy dominants. These findings highlight the multifaceted challenges posed to forests by extreme heat waves, and the need to better understand their impact on forest ecosystems in a rapidly warming climate.

Pollen Assisted Migration Faces Its Own Challenges - Gregory A. O'Neill; Glenn T. Howe; Sally N. Aitken (Global Change Biology, 2025)

The 1912 Douglas-Fir Heredity Study: Long-Term Effects of Climatic Transfer Distance on Growth and Survival - J Bradley St. Clair; Glenn T Howe; Jennifer G Kling (Journal of Forestry, 2020)
The 1912 Douglas-Fir Heredity Study is one of the first studies undertaken by the US Forest Service, and one of the first forest genetics studies in North America. The study considers provenance variation of 120 parent trees from 13 seed sources planted at five test sites in the Pacific Northwest. The unique, long-term nature of the study makes it valuable to revisit and consider its biological and historical significance. This analysis considers how far climatically Douglas-fir populations may be moved without incurring unacceptable declines in growth and survival. Results indicate that Douglas-fir seed sources may be moved at least 2° C cooler or warmer and still retain good long-term survival and productivity. However, projected future climate change beyond 2° C may lead to lower survival and productivity. One option to address these concerns is assisted migration; however, if seed sources are moved beyond 2–3° C to a cooler climate in anticipation of warming, or from a more continental to a maritime climate, we are likely to see increased mortality and associated losses in productivity in the near-term. Lessons from this study include: (1) pay attention to good experimental design; we were able to overcome limitations from the design by using new statistical approaches; (2) maladaptation may take time to develop; poorer survival was not evident until more than two decades after planting; and (3) long-term studies may have value for addressing new, unforeseen issues in the future.

Risk of genetic maladaptation due to climate change in three major European tree species - Aline Frank; Glenn T. Howe; Christoph Sperisen; Peter Brang; J. Bradley St. Clair; Dirk R. Schmatz; Caroline Heiri (Global Change Biology, 2017)
Tree populations usually show adaptations to their local environments as a result of natural selection. As climates change, populations can become locally maladapted and decline in fitness. Evaluating the expected degree of genetic maladaptation due to climate change will allow forest managers to assess forest vulnerability, and develop strategies to preserve forest health and productivity. We studied potential genetic maladaptation to future climates in three major European tree species, Norway spruce ( Picea abies ), silver fir ( Abies alba ), and European beech ( Fagus sylvatica ). A common garden experiment was conducted to evaluate the quantitative genetic variation in growth and phenology of seedlings from 77 to 92 native populations of each species from across Switzerland. We used multivariate genecological models to associate population variation with past seed source climates, and to estimate relative risk of maladaptation to current and future climates based on key phenotypic traits and three regional climate projections within the A1B scenario. Current risks from climate change were similar to average risks from current seed transfer practices. For all three climate models, future risks increased in spruce and beech until the end of the century, but remained low in fir. Largest average risks associated with climate projections for the period 2061–2090 were found for spruce seedling height (0.64), and for beech bud break and leaf senescence (0.52 and 0.46). Future risks for spruce were high across Switzerland. However, areas of high risk were also found in drought‐prone regions for beech and in the southern Alps for fir. Genetic maladaptation to future climates is likely to become a problem for spruce and beech by the end of this century, but probably not for fir. Consequently, forest management strategies should be adjusted in the study area for spruce and beech to maintain productive and healthy forests in the future.

Distinct genecological patterns in seedlings of N orway spruce and silver fir from a mountainous landscape - Aline Frank; Christoph Sperisen; Glenn Thomas Howe; Peter Brang; Lorenz Walthert; John Bradley St.Clair; Caroline Heiri (Ecology, 2017)
Understanding the genecology of forest trees is critical for gene conservation, for predicting the effects of climate change and climate change adaptation, and for successful reforestation. Although common genecological patterns have emerged, species‐specific details are also important. Which species are most vulnerable to climate change? Which are the most important adaptive traits and environmental drivers of natural selection? Even though species have been classified as adaptive specialists vs. adaptive generalists, large‐scale studies comparing different species in the same experiment are rare. We studied the genecology of Norway spruce ( Picea abies ) and silver fir ( Abies alba ), two co‐occurring but ecologically distinct European conifers in Central Europe. For each species, we collected seed from more than 90 populations across Switzerland, established a seedling common‐garden test, and developed genecological models that associate population variation in seedling growth and phenology to climate, soil properties, and site water balance. Population differentiation and associations between seedling traits and environmental variables were much stronger for Norway spruce than for silver fir, and stronger for seedling height growth than for bud phenology. In Norway spruce, height growth and second flushing were strongly associated with temperature and elevation, with seedlings from the lowlands being taller and more prone to second flush than seedlings from the Alps. In silver fir, height growth was more weakly associated with temperature and elevation, but also associated with water availability. Soil characteristics explained little population variation in both species. We conclude that Norway spruce has become an adaptive specialist because trade‐offs between rapid juvenile growth and frost avoidance have subjected it to strong diversifying natural selection based on temperature. In contrast, because silver fir has a more conservative growth habit, it has evolved to become an adaptive generalist. This study demonstrates that co‐occurring tree species can develop very different adaptive strategies under identical environmental conditions, and suggests that Norway spruce might be more vulnerable to future maladaptation due to rapid climate change than silver fir.

High-density miniaturized seed orchards of Douglas-fir - Scott E. Kolpak; Jim Smith; Michael J. Albrecht; Jeff DeBell; Sara Lipow; Marilyn L. Cherry; Glenn T. Howe (New Forests, 2015)

Conifer DBMagic: a database housing multiple de novo transcriptome assemblies for 12 diverse conifer species - W. Walter Lorenz; Savavanaraj Ayyampalayam; John M. Bordeaux; Glenn T. Howe; Kathleen D. Jermstad; David B. Neale; Deborah L. Rogers; Jeffrey F. D. Dean (Tree Genetics & Genomes, 2012)

Genetic maladaptation of coastal Douglas‐fir seedlings to future climates - J. BRADLEY ST CLAIR; GLENN T. HOWE (Global Change Biology, 2007)
Climates are expected to warm considerably over the next century, resulting in expectations that plant populations will not be adapted to future climates. We estimated the risk of maladaptation of current populations of coastal Douglas‐fir ( Pseudotsuga menziesii var. menziesii ) to future climates as the proportion of nonoverlap between two normal distributions where the means and genetic variances of current and future populations are determined from genecological models derived from seedling common garden studies. The risk of maladaptation was large for most traits when compared with the risk associated with current transfers within seed zones, particularly for the more drastic climate change scenario. For example, the proportion of nonoverlap for a composite trait representing bud set, emergence, growth, and root : shoot ratio was as high as 0.90. We recommend augmenting within‐population variation by mixing local populations with some proportion of populations from lower elevations and further south. Populations expected to be adapted to climates a century from now come from locations as far down in elevation as 450–1130 m and as far south in latitude as 1.8–4.9°.

Public Influences on Plantation Forestry - Glenn T. Howe; Bruce Shindler; Benjamin Cashore; Eric Hansen; Denise Lach; Ward Armstrong (Journal of Forestry, 2005)
For plantation forestry to be successful, it must be biologically possible, economically feasible, and culturally adoptable (i.e., socially acceptable). We discuss social acceptability and plantation forestry in the Pacific Northwest, stressing that social acceptability is a judgmental process that is both provisional and dependent on many complex factors, and that most decisions are based on intuition, rather than a rational evaluation of all relevant choices. We suggest that conflicts over plantation forestry can be minimized by carefully considering social acceptability and by forging formal agreements (accords) that promote the goals of both environmentalists and forest industries.